Interrogating Youths’ Involvement in Politics and Implications on Violence in Nigeria - Babatunde Joshua Omotosho (Modern Africa, 2023)
Protests, whether violent or non-violent are part of the instruments deployed by youths to express their dissatisfaction with poor governance and non-inclusion in decision-making in Nigeria. To the youths, their relevance in politics seems to begin during election and terminates as soon as elections are over. Changing this narrative becomes critical for these youths in order to enable them to utilise their potentials and contribute to national development. This scenario raises a number of questions: what have been the activities of youths within political spaces and decision-making over the years? Are they involved or excluded and why? The present article interrogates these and other issues and makes suggestions on how youths’ potentials in Nigeria can be properly harnessed, developed and utilised for the benefits of both youths and the citizenry as a whole.